Caffeine supplementation for soccer: A review of strengths, limitations, and knowledge gaps - Tallis, J.; Duncan, M.; Richardson, D.; Clarke, N.; Guimarães-Ferreira, L. (International Journal of Sports Medicine, 2025)
Caffeine is a well-established ergogenic aid with a wealth of evidence demonstrating beneficial effects for physical performance, cognitive function and sport specific skills. Intuitively, it may be considered that such effects may translate to improved soccer specific performance, however, evidence examining the effects of caffeine on the interacting demands of soccer match play is sparse. Given that caffeine supplementation is highly prevalent in professional soccer, and in a number of cases practices adopted lack supporting evidence, this review evaluates the current state of the knowledge regarding the ergogenic potential of acute caffeine consumption specifically for soccer performance. Furthermore, this review identifies knowledge gaps to guide future research, and whilst considering the unique environmental constraints, uses the available evidence to develop practical guidelines for safe and effective use.